Post-Transplant Treatment in Liver Cirrhosis Patients: A Comprehensive Review (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Liver cirrhosis, characterized by progressive liver damage and fibrosis, frequently culminates in liver failure, often necessitating liver transplantation as the only curative treatment. Following transplantation, the post-transplant period plays a crucial role in ensuring patient survival and graft function. This article reviews post-transplant care for liver cirrhosis patients, focusing on immunosuppressive therapy, prevention of infections, management of graft rejection, and treatment of long-term complications such as cardiovascular diseases and malignancies. While immunosuppressive therapy has dramatically improved graft survival, it presents challenges such as nephrotoxicity and an increased risk of infection. Moreover, long-term issues like graft fibrosis, cardiovascular diseases, and post-transplant malignancies pose ongoing risks. This review also highlights the importance of personalized treatment regimens based on patient characteristics and explores recent advances in immunosuppressive agents, infection prophylaxis, and the management of long-term complications. The article concludes with recommendations for future research, emphasizing the need to improve treatment strategies and optimize patient outcomes.